Religious Maturity Judging from Emotional Maturity - Rike Adelia Hermawan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine how the religious maturity of an individual relates to emotional maturity. This study uses the Library Research method, by collecting data and information from various books and related journals. After conducting the research, it was concluded that religious maturity is a person's ability to recognize or understand religious values, which lie in their noble values, and incorporate those values into attitude and behavior. Religious maturity is influenced by internal factors in the form of a person's level or absorption of religious values, one's interpretation of religious teachings, and one's emotional maturity. External factors influencing religious maturity include the way family and environment transfer and internalize religious values and teachings to someone. Parents, in particular, are the parties who help shape the emotional maturity of children, even before the child is born. A person's emotional maturity not only impacts themselves but also affects how they practice religious values. Emotional maturity is a state or condition of reaching a mature level of emotional development, and therefore the person concerned no longer displays emotional patterns appropriate for children. Factors that can affect a person's emotional maturity include age, physical and glandular changes, parental care, environment, and gender. The main impact of emotional maturity on religious maturity is actually the greatest influence on how one understands religion, which not only contains doctrines that must be obeyed but also values that must be believed and applied in everyday life.